Discovery of the novel HLA‐DRB1*09:01:08 allele in a Taiwanese volunteer bone marrow donor and identification of the probable HLA‐A, HLA‐B and HLA‐DRB1 haplotype in association with DRB1*09:01:08. (26th July 2012) - Yang, K. L.; Lee, S. K.; Yang, S. Y.; Kao, R. H.; Lin, C. L.; Lin, P. Y.
Summary We report here the novel variant of HLA‐DRB1*09:01, DRB1*09:01:08, discovered in a Taiwanese volunteer bone marrow donor by a sequence‐based typing (SBT) method. The DNA sequence of DRB1*09:01:08 is identical to the sequence of DRB1*09:01:02 in exon 2 except a silent mutation at nucleotide position 261(C→T) (GCC→GCT at codon 58). We hypothesize DRB1*09:01:08 was probably derived from DRB1*09:01:02 via a nucleotide point mutation event. The plausible HLA‐A, HLA‐B and HLA‐DRB1 haplotype in association with DRB1*09:01:08 was deduced as A*02:07‐B*46:01‐DRB1*09:01:08.